»Hvad gör väl namnet?«: Anonymitet och varumärkesbyggande i 1840-talets svenska press och parnass - Arping, Åsa (Tidskrift för litteraturvetenskap, 2010)
»What’s in a Name?«: Anonymity and Brand making in the Swedish Press and Helicon of the 1840’s Foregrounding Sweden in the 1840’s as a »transformational society« (A. Melberg), politically pendling between revolution and reaction, this article explores the symbolic re-negotiations of the name in contemporary press and book market. During this decade dominating practices of anonymous publishing and collective voices addressing »public opinion« were challenged by new demands for individualized image-making. How did writers and critics deal with this transformation, and how did it affect their public appearance? These questions are exemplified through writers and/or cultural journalists like Fredrika Bremer, Sophie von Knorring, Emilie Carlén, C.J.L. Almqvist, Oscar Patric Sturzenbecker, Wendela Hebbe and Carl Anton Wetterbergh. Confronting the persistent use of anonymity, the essay argues for a more thorough understanding of how this practice, rather than offering concealment and protection, was diligently exploited as a means to destabilize the role of the writer/journalist, often boosting public interest in the private person behind the text. For women participants, anonymous writing meant conforming to prescribed norms of female modesty, but at the same time it offered possibilities to transgress them. In the same way, choosing not to publish in print was more than an act of humility, exclusive manucript circulation could just as well function as a critique of literary commerce. As today’s digital blog activities have made evident, scholars of literature and press must include non-print material in their analyses. Similarly an interest in the public literary debates of the 1840’s necessitates an awareness of an ongoing, parallel semi-public presence of manuscripts and letters, in order to understand how actors move between different spheres of literary production and circulation. Thus, the significance of the name in literary publicities is apparent, and should attract further attention in our field of research.